Gender-Associated Outcomes Following Percutaneous Coronary Intervention With a Third-Generation, Ultrathin-Strut Drug-Eluting Stent: A Real-World, Single-Center Experience - Gili, Sebastiano; Galli, Stefano; Teruzzi, Giovanni; Santagostino Baldi, Giulia; Ravagnani, Paolo; Fabbiocchi, Franco; Bartorelli, Antonio; Montorsi, Piero; Trabattoni, Daniela (Frontiers in Cardiovascular Medicine, 2022)
Introduction. In recent years the new third-generation, the ultrathin bioresorbable-polymer sirolimus-eluting stent (BP-SES), has been introduced for the treatment of coronary artery disease (CAD). Aim of the present study was to assess different clinical outcomes and safety of this drug-eluting stent in male and female patients in a real-world setting. Methods. The present study is a retrospective analysis including all patients treated with BP-SES between January 2017 and December 2019 at a single, high-volume center. Follow-up data, including stress test results and clinical setting, were collected during outpatient visits or by telephone contact. Patients symptomatic for angina or with a positive stress test were addressed to CT scan/coronary angiogram. Main study outcome was target lesion failure (TLF), defined as a composite of cardiovascular death, target vessel myocardial infarction or target lesion revascularization. Results: Overall, 66 (15.9%) female and 349 (84.1%) male patients were included; women were older (median age 70 vs. 66, p=0.003) and with lower BMI (25.0 vs. 26.1, p=0.010) compared to men, with no other relevant differences in baseline characteristics. Indication for percutaneous coronary intervention (PCI) was acute coronary syndrome in 86 (20.7%) of the cases, with no significant differences between male and female patients. A total of 558 lesions were treated with BP-SES stents, 90 in women and 468 in men (1.36 vs. 1.34 lesions per patient, p=0.83); cumulative stent length (33.6 mm vs. 38.4 mm, p=0.078) and mean stent diameter (2.92 mm vs. 3.0 mm, p=0.39) did not differ in women compared to men. Technical and clinical success was achieved in all patients. Stent thrombosis (ST) occurred in 2 (0.5%) patients, both males. TLF occurred in 10 (2.9%) men and in 2 (3.0%) women after a median follow-up of 402 days, without significant differences at log-rank analysis (2.34 events per 100 patient-years in males, 2.53 in females; p=0.80). Conclusions. Ultrathin struts BP-SES showed a safe and effective option for the treatment of CAD in both women and men, with a very low ST rate and favorable long-term outcomes.